2022
DOI: 10.3390/jcm11216396
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Oral Parafunctional and Postural Habits and the Symptoms of Temporomandibular Disorders: A Survey-Based Cross-Sectional Cohort Study Using Propensity Score Matching Analysis

Abstract: Temporomandibular disorders (TMDs) are a multifactorial joint disease of the masticatory system. The possible etiological factors involved in the onset and progression of TMDs include oral parafunctional habits (OPFHs) and postural habits (PHs). However, little information is available on the association between OPFHs and PHs and a predisposition to TMDs. Thus, to investigate whether the presence of OPFH and PH predisposes individuals to TMDs, a survey-based cross-sectional cohort study of self-reported TMD wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The stabilization splints may result in a neuromuscular balance, removing posterior interferences and supplying a stable occlusal relationship and centric relation. The relationship between craniometrical posture and TMDs has been studied; however, despite the huge number of studies, clinicians and academics remain unconvinced [ 24 ]. There is evidence from certain studies that people with TMDs have altered head and cervical spine posture, while no such link is found in other investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The stabilization splints may result in a neuromuscular balance, removing posterior interferences and supplying a stable occlusal relationship and centric relation. The relationship between craniometrical posture and TMDs has been studied; however, despite the huge number of studies, clinicians and academics remain unconvinced [ 24 ]. There is evidence from certain studies that people with TMDs have altered head and cervical spine posture, while no such link is found in other investigations.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 18 , 29 Injury to the structures related to the orofacial region may cause disorders that inflict orofacial pain. 33 , 34 Anxiety has also been reported to elevate cytokines level, which would be related to pain by its ability to promote inflammatory response and leading to pain symptoms. 32 Several studies suggested that anxiety is thought to have a pain catastrophizing effect, where a study on chronic musculoskeletal pain revealed that higher anxiety level was associated to higher pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“… 13 These behaviors have been implicated as potential risk factors for TMDs. 14 The temporomandibular region features neural and biomechanical connections that form a complex functional unit, with studies suggesting that neural pathways associated with PT can be influenced by posture. 15 Interestingly, PT appears to be associated with Parkinson’s disease, possibly due to the clenching or grinding of teeth caused by muscle rigidity, spasm and jaw tremors caused by uncoordinated muscle contractions.…”
Section: Introductionmentioning
confidence: 99%